Evaluación de la formación en educación sexual integral y consumo de pornografía en estudiantes de universidad de España (Investigaciones) - Gutiérrez García, Andrea (2024)
The consumption of pornography is becoming an increasing problem among teenagers and even children, often leading to addiction. Recent studies indicate that exposure to this content begins before puberty, which raises serious concerns about its impact on the development and well-being of youth, as well as on their socialization and conception of gender equality. This article will present the results of a study conducted with 647 students from the University of La Rioja (Spain), evaluating both their pornography consumption patterns and their perception and satisfaction with the sexual education received. The results show the practical absence of this training and the generalized total or partial dissatisfaction with it when it is carried out. Likewise, there is a high consumption of pornography, especially in the case of men, which in the absence of adequate sexual education becomes a source of distorted information.